2009
DOI: 10.1002/ajp.20708
|View full text |Cite
|
Sign up to set email alerts
|

Validation of salivary cortisol and testosterone assays in chimpanzees by liquid chromatography‐tandem mass spectrometry

Abstract: Owing to its high temporal sensitivity, saliva has distinct advantages for measuring steroids, compared with other noninvasive samples such as urine and feces. Here, we report the validity of assaying salivary cortisol (C) and testosterone (T) using liquid chromatography-tandem mass spectrometry (LC-MS/MS) in captive male chimpanzees, Pan troglodytes. For both the C and T concentrations, we found positive relationships between saliva and plasma. The concentrations of C and T in saliva showed clear patterns of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 47 publications
3
40
0
2
Order By: Relevance
“…Measurements using LC-MS/MS (20,21) (Fig. 8A) and ELISA (data not shown) both showed that similar in WT dams carrying WT fetuses, a drastic decrease in the progesterone level was observed in Nrk-null dams carrying Nrk-null fetuses: whereas the level ranged between ϳ20 and ϳ100 ng/ml at 17.5 dpc, it ranged between ϳ1 and ϳ2 ng/ml in five of seven mice at 19.5 dpc.…”
Section: Nrk Is Not Expressed In Reproductive Tissuesmentioning
confidence: 89%
“…Measurements using LC-MS/MS (20,21) (Fig. 8A) and ELISA (data not shown) both showed that similar in WT dams carrying WT fetuses, a drastic decrease in the progesterone level was observed in Nrk-null dams carrying Nrk-null fetuses: whereas the level ranged between ϳ20 and ϳ100 ng/ml at 17.5 dpc, it ranged between ϳ1 and ϳ2 ng/ml in five of seven mice at 19.5 dpc.…”
Section: Nrk Is Not Expressed In Reproductive Tissuesmentioning
confidence: 89%
“…the methods used for LC-Ms/Ms device were essentially similar to those described previously [9,24]. Specificity: Zero saliva (1 mL) and serum (0.1 mL) from healthy males (1 mL) were extracted, as described above.…”
Section: Validation For the Simultaneous Quantification Of T And F Inmentioning
confidence: 99%
“…Saliva T level are ~ 100 pg/mL or less and the steroid-binding protein levels are low; therefore, adsorption to instruments is a problem. When a linen rope is used for chimpanzee saliva collection, the rate of F adsorption is approximately 10% [9,29]. Furthermore, cotton used in a container for We developed a method for simultaneous quantification of T and F in saliva using LC-MS/MS [9,24], which has high specificity, sensitivity, and accuracy in the micro-quantification of steroid hormones.…”
Section: Absolute Ranges Of Total Bioavailable and Free T And F Valmentioning
confidence: 99%
See 2 more Smart Citations